Decoding sentiment: Methodology behind SAFE's Manager Sentiment Index - Sara Fadavi; Alexander Hillert (Leibniz Institute for Financial Research SAFE, 2024)
SAFE's monthly Manager Sentiment Index is constructed by extracting sentiment from corporate financial disclosures of listed companies in Germany, offering significant insights into top management's perspectives. This white paper outlines the methodology behind the index and its financial implications. Information about managers' assessment of firms' performance and financial conditions is material to investors but, at the same time, hard to observe. The SAFE Manager Sentiment Index quantifies managers' beliefs using textual analysis of financial reports and earnings conference call transcripts. We show that the index is a strong predictor of future stock market returns. In summary, the SAFE Manager Sentiment Index provides a practical tool for key stakeholders such as investors, analysts, and policymakers seeking timely signals of corporate sentiment.
Keywords: 330; Manager Sentiment; Textual Analysis; Financial Disclosures; Return Predictability